Saturday

April 19, 2014

April 19, 2014

Posted by **Janet** on Sunday, August 22, 2010 at 10:09pm.

(x/(x+1))+ ((2x-2)/x) = -1/(x+1)

can someone show it step by step so i can understand it? Thanks!

- Math -
**Michael**, Sunday, August 22, 2010 at 10:43pm(x/(x+1))+ ((2x-2)/x) = -1/(x+1)

((2x-2)/x) = -1/(x+1) -x/(x+1)

((2x-2)/x) = (-1-x)/(x+1)

((2x-2)/x) = -(x+1)/(x+1)

((2x-2)/x) = -1

2x-2 = -x

2x+x = 2

3x = 2

x = 2/3

**Related Questions**

math ergent please please... - 10.a)Solve the inequality x^3-5x^2+2x+8<0 by i...

algebra - solve by using the quadratic formula prove your answer is correct by ...

TRIGONOMETRY - I don't understand how to convert -3-4i to polar coordinates. I ...

algebra - Solve by substitution method 3x+8y=17 2x+y=14 please show step by step...

math - can you show me how to solve linear systems step by step????? 2x+y=5 x-y=...

math - please show me how to solve this equation.I need step by step, because I ...

Math - Can someone show me step by step on how to factor/solve this problem ...

math - Can someone please show me step by step how to solve this, I've been ...

math - how do you solve the exponential equation, 12^x = 14^3x? If someone could...

math - can someone explain step by step to solve system equations and example ...